Analysis of service management structures in companies from the service sector (2016)
The study that guided this article was done with the purpose of evaluating different service approaches that are articulated as part of the strategies that guide the philosophy of eight organizations. To achieve this, different theoretical perspectives about the service are used, and with the method of case study eight successful companies from Antioquia that developed their organizational structures for service management are studied. The review using models obtained by the literature and the comparison of each case study approaches, allowed to find similarities that can set some guidelines to follow in formulating a service structure, considered as a strategy of differentiation and success factor. The study gives an idea of how to implement models to analyse and evaluate the performance of service, which in future can also be studied from clients / customers. The limitations are related to the recent use of the concept of “servitization” practices which are still subject of discussion